Students’ Competence in Using Causative Verb (Case Study to the Fifth Semester Students of English Department at UMMU) - Erwin Gay; Lily Shantra (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
Learning English, especially grammar, is very difficult because grammar has confusing rules to learn. Many students even have problems using causative verb, especially in make, have and get causative sections. Therefore,this study aims to find out how well the students’ abilities in using causative verb. The method used in this study is descriptive qualitative research method.This method tends to analyze data inductive. Besides that, the instrument that used by the researcher was question sheet. The researcher used multiple choice to know the students’ competence in using causative verb. The results of this study indicate that the competences of students of Muhammadiyah University is in the very low category, it can be seen from the students test results, that is 13,3 %.It is hoped that the study will be useful theoretically for researchers and learners and practically for teachers and syllabus designers.